Optimalisasi Produktivitas Karyawan Melalui Perbaikan Lingkungan Kerja - Warman, Defi (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
Based on the test results on the work environment variables have a significant effect on employee productivity in the Production Division of the Saudara Ngadjunjung Rasa (Sdr) Bread Factory in Kualu Village, Kampar Regency, this is proven based on the t-test found t-count is greater than t-table (4.981> 2.017). The magnitude of the influence of the work environment variables on the productivity variable is 0.366 (36.6%) this is proven based on the results of the determination test where the R2 value is 0.366. The recommendation that can be submitted is for the company to further improve and fix the lighting problem in the workplace because this gets the lowest response from respondents.